2012
DOI: 10.4236/mps.2012.24020
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Injection Techniques in the Treatment of Trigger Finger

Abstract: Background: Trigger finger is characterized by the inability to smoothly flex and extend the digit. Corticosteroids are an accepted non-surgical treatment option and can be delivered via two techniques. While the palmar approach is more commonly used, some have suggested that the mid-axial approach may be less painful for patients and yield higher intrasheath injection rates. The purpose of this study is to compare the accuracy of the palmar and midaxial approaches for delivery of corticosteroids into the flex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…1,3,4 Pain in the finger may be felt on finger flexion and may radiate to the proximal interphalangeal (PIP) and metacarpophalangeal (MTP). 5,6 Most common cause trigger finger is overuse trauma of the hands from gripping with increased pull on the flexor tendon. The diagnostic is made by palpation and identification of localized tenderness and swelling of the volar tendon sheats, but ultrasound can be used when there are a clinical doubt and diagnostic can be made with hyperechoic lesion with cut-off thickness of 0.62 mm proposed to distinguish a disease from a healthy one, MRI for exclusion of secondary causes in younger patient and plain radiograph (in particular case) which is history of trauma.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,4 Pain in the finger may be felt on finger flexion and may radiate to the proximal interphalangeal (PIP) and metacarpophalangeal (MTP). 5,6 Most common cause trigger finger is overuse trauma of the hands from gripping with increased pull on the flexor tendon. The diagnostic is made by palpation and identification of localized tenderness and swelling of the volar tendon sheats, but ultrasound can be used when there are a clinical doubt and diagnostic can be made with hyperechoic lesion with cut-off thickness of 0.62 mm proposed to distinguish a disease from a healthy one, MRI for exclusion of secondary causes in younger patient and plain radiograph (in particular case) which is history of trauma.…”
Section: Discussionmentioning
confidence: 99%
“…The 2 techniques have been found equivalent in delivering medication into the sheath but have not been compared clinically. 20 Kamhim and colleagues 21 demonstrated that injections reach the intrasheath compartment in only 50% of attempts, giving rise to the notion that medication does not need to be in the sheath to be effective. Taras and colleagues 22 compared groups of intrasheath and extrasheath injections and, in contrast to popular belief, found that the extrasheath cohort had better outcomes.…”
Section: Nonsurgical Treatmentmentioning
confidence: 96%
“…It is important to accurately inject the steroid into the flexor tendon sheath to increase the therapeutic effect of steroids and reduce side effects such as tendon rupture, skin atrophy, and discoloration, which can occur because of local injection [8,9]. However, there is only a 36% to 49% probability that the drug will be accurately injected into the flexor tendon sheath during actual steroid injection [10,11], and only a few studies have reported the steroid injection technique and its clinical results in trigger finger.…”
Section: Introductionmentioning
confidence: 99%